Tribute to Dato’ Ir. Kam U-Tee the man who contributed to the success of Penang water authority - Lee, Yow Ching, Dato Ir. Dr (The Institution of Engineers, Malaysia (IEM), 2017)
Link to publisher’s homepage at http://www.myiem.org